2010
DOI: 10.1128/aac.00495-10
|View full text |Cite
|
Sign up to set email alerts
|

The Virucidal EB Peptide Protects Host Cells from Herpes Simplex Virus Type 1 Infection in the Presence of Serum Albumin and Aggregates Proteins in a Detergent-Like Manner

Abstract: The linear cationic amphiphilic EB peptide, derived from the FGF4 signal sequence, was previously shown to be virucidal and to block herpes simplex type I (HSV-1) entry (H. Bultmann, J. S. Busse, and C. R. Brandt, J. Virol. 75:2634؊2645, 2001). Here we show that cells treated with EB (RRKKAAVALLPAVLLALLAP) for less than 5 min are also protected from infection with HSV-1. Though protection was lost over a period of 5 to 8 h, it was reinduced as rapidly as during the initial treatment. Below a 20 M concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Although their mechanism of action is seldom studied at the molecular level, some of these compounds interfere with the lipid envelope of HSVs, which can be evidenced by transmission electron microscopy (TEM) (Popkin et al, 2017 ). Interestingly, numerous compounds with virucidal activity have been identified both, derived from natural and non-natural sources (Schuhmacher et al, 2003 ; Schnitzler et al, 2007 ; Bultmann et al, 2010 ; Houston et al, 2017 ; Pradhan and Nguyen, 2018 ). Importantly, the identification of virucidal activity in an antiviral compound requires that the virus be treated alone with the drug for a defined period of time and then that the latter be washed before probing the infectivity of the virus over susceptible cells.…”
Section: Virion Structure and Compositionmentioning
confidence: 99%
“…Although their mechanism of action is seldom studied at the molecular level, some of these compounds interfere with the lipid envelope of HSVs, which can be evidenced by transmission electron microscopy (TEM) (Popkin et al, 2017 ). Interestingly, numerous compounds with virucidal activity have been identified both, derived from natural and non-natural sources (Schuhmacher et al, 2003 ; Schnitzler et al, 2007 ; Bultmann et al, 2010 ; Houston et al, 2017 ; Pradhan and Nguyen, 2018 ). Importantly, the identification of virucidal activity in an antiviral compound requires that the virus be treated alone with the drug for a defined period of time and then that the latter be washed before probing the infectivity of the virus over susceptible cells.…”
Section: Virion Structure and Compositionmentioning
confidence: 99%
“…EB inhibits numerous unrelated viruses, including herpes simplex virus [28], influenza virus [106] and vaccinia (small pox) virus [107], consistent with inhibition that is dependent on peptide physical chemistry, rather than on sequence-specific interactions with viral fusion proteins. Inhibition of viral entry by EB occurs at an early stage, likely by inhibition of fusion [108,109]. Brandt and colleagues showed that EB pre-incubation protected cells from virus, showing that the peptide binds to, or enters, cells [108,109].…”
Section: Accidental Identification Of Peptide Entry Inhibitorsmentioning
confidence: 99%
“…Inhibition of viral entry by EB occurs at an early stage, likely by inhibition of fusion [108,109]. Brandt and colleagues showed that EB pre-incubation protected cells from virus, showing that the peptide binds to, or enters, cells [108,109]. They also showed that EB causes aggregation of both viruses and various proteins, driven by the hydrophobic C-terminal tail of the peptide [108,109].…”
Section: Accidental Identification Of Peptide Entry Inhibitorsmentioning
confidence: 99%
“…The authors developed a FGF4 signal peptide modified with a highly cationic tetramer at the N-terminus [94]. The resulting peptide, given that BSA was present in the serum at sufficient concentrations, demonstrated the ability to block HSV-1 entry by binding to free virions [94,95]. Another study reported that using small peptides with differing cationic charge distributions could bind to HS and block gD [96].…”
Section: Emerging Therapy: Cationic Peptide Therapiesmentioning
confidence: 99%